Tumor-Evoked Sensitization of C Nociceptors: A Role for Endothelin - Hamamoto, Darryl T. (American Physiological Society, 2008)
Primary and metastatic cancers that effect bone are frequently associated with pain. Sensitization of primary afferent C nociceptors innervating tissue near the tumor likely contributes to the chronic pain and hyperalgesia accompanying this condition. This study focused on the role of the endogenous peptide endothelin-1 (ET-1) as a potential peripheral algogen implicated in the process of cancer pain. Electrophysiological response properties, including ongoing activity and responses evoked by heat stimuli, of C nociceptors were recorded in vivo from the tibial nerve in anesthetized control mice and mice exhibiting mechanical hyperalgesia following implantation of fibrosarcoma cells into and around the calcaneus bone. ET-1 (100 μM) injected into the receptive fields of C nociceptors innervating the plantar surface of the hind paw evoked an increase in ongoing activity in both control and tumor-bearing mice. Moreover, the selective ET(A) receptor antagonist, BQ-123 (3 mM), attenuated tumor-evoked ongoing activity in tumor-bearing mice. Whereas ET-1 produced sensitization of C nociceptors to heat stimuli in control mice, C nociceptors in tumor-bearing mice were sensitized to heat, and their responses were not further increased by ET-1. Importantly, administration of BQ-123 attenuated tumor-evoked sensitization of C nociceptors to heat. We conclude that ET-1 at the tumor site contributes to tumor-evoked excitation and sensitization of C nociceptors through an ET(A) receptor mediated mechanism.